2011
DOI: 10.1021/ja203133h
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonally Dual-Clickable Janus Nanoparticles via a Cyclic Templating Strategy

Abstract: Synthetic asymmetrical systems, Janus particles and patchy particles, are capable of undergoing hierarchical assembly processes that mimic those of Nature, to serve as switchable devices, optical probes, phase-transfer catalysts and multi-functional drug carriers, each of which benefits from opposing surface patterns behaving differently. Production of nanometer-sized Janus particles that are equipped with efficient chemistries remains a challenge. A robust Janus-faced polymer nanoparticle framework that prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 39 publications
0
51
0
Order By: Relevance
“…36 GPC traces of the PEGylated copolymer 7 and its precursor 6 (Fig. 4) demonstrated that the grafting of PEG in water was successful.…”
mentioning
confidence: 92%
“…36 GPC traces of the PEGylated copolymer 7 and its precursor 6 (Fig. 4) demonstrated that the grafting of PEG in water was successful.…”
mentioning
confidence: 92%
“…Copyright 2012, Royal Society of Chemistry. Panel (F) reproduced with permission 36. Copyright 2011, American Chemical Society.…”
Section: Preparation Of Janus Particlesmentioning
confidence: 99%
“…Masking techniques involve the protection of one part of a preformed particle to selectively functionalize the exposed face. Protection can be carried out by adsorption over flat substrates35 or particles,36 by microcontact printing methods37 and with Pickering emulsions 19. As an example, Eriksson et al recently reported the electrochemical oxidation of thiolated non‐conductive magnetic beads 35.…”
Section: Preparation Of Janus Particlesmentioning
confidence: 99%
“…Furthermore, another bioconjugation reaction between maleimides and thiols is also efficient because the reaction can be performed under physiologically relevant solvents and form a stable covalent linkage . Therefore, consecutive bioconjugation reactions executed by a maleimide‐thiol coupling reaction and Huisgen 1,3‐dipolar cycloaddition could be employed to prepare anisotropic biohybrid microparticles (MPs) with two different biomolecules spatio‐selectively conjugated on each compartment for multiplexing biodetection applications …”
Section: Introductionmentioning
confidence: 99%